(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to analyze the processes that allow students to develop reading comprehension through extrapolation. A mixed methodology was used, where through the descriptive correlational analysis between the study variables and the qualitative one that allowed describing and explaining the pedagogical processes carried out. Regarding the quantitative method, a purposive sample of 220 students from the engineering area of a public university in Lima, Peru, whose ages ranged from 16 to 20 years old, of both genders, was used. For the qualitative analysis, eight students were randomly selected. The results showed that the dimensions referring to reading comprehension had an average value of 53% and the correlational analysis indicated a positive and regular average relationship between reading comprehension and extrapolation (Spearman’s rho = .394). It was concluded that the use of extrapolation for the development of reading comprehension has been positive, reaching significant levels.